2018
DOI: 10.1111/tid.12963
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of chronic suppressive azole therapy for endemic fungal infections in solid organ transplant recipients

Abstract: Chronic suppressive azole therapy was safe and effective in preventing reactivation of EFI in SOT recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We screened 548 studies, of which 197 fulfilled criteria [ 2–197 ]. Of these, 4 included a review of related literature [ 2–4 , 198 ], 15 were cohort studies [ 10 , 32 , 47 , 53 , 54 , 56 , 57 , 62 , 63 , 71 , 89 , 100 , 184 , 185 , 187 ], and the majority were case reports. After careful review of references, 1 cohort [ 1 ] and 42 additional case reports or series were identified [ 199–213 ] including 20 [ 188 , 190 , 192 , 214–230 ] from a prior review [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We screened 548 studies, of which 197 fulfilled criteria [ 2–197 ]. Of these, 4 included a review of related literature [ 2–4 , 198 ], 15 were cohort studies [ 10 , 32 , 47 , 53 , 54 , 56 , 57 , 62 , 63 , 71 , 89 , 100 , 184 , 185 , 187 ], and the majority were case reports. After careful review of references, 1 cohort [ 1 ] and 42 additional case reports or series were identified [ 199–213 ] including 20 [ 188 , 190 , 192 , 214–230 ] from a prior review [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among 16 cohort studies, 3 reported on blastomycosis [ 56 , 62 , 63 ], 5 on coccidioidomycosis [ 10 , 32 , 47 , 53 , 71 ], and 4 on histoplasmosis [ 1 , 54 , 89 , 248 ], and 4 evaluated a mixture of endemic mycoses [ 57 , 184 , 185 , 187 ]. The majority of cohorts were single-institution studies, except for 4 [ 47 , 57 , 184 , 185 ] that involved multiple institutions and included surveillance data [ 184 ], or registry data [ 185 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation